2018
DOI: 10.1186/s12954-018-0210-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of HIV infection among men who inject drugs in a remote area of Vietnam

Abstract: BackgroundLack of information on the HIV epidemic among men who inject drugs (MWID) in northwestern Vietnam, a remote area, may hamper national efforts to control the disease. We examined HIV prevalence, needle–syringe sharing behaviors, and associated factors among MWID in three areas of northwestern Vietnam.MethodsWe used descriptive analysis to report the characteristics, frequency of risk behaviors, and of access to healthcare services among the MWID. Univariable logistic regression was used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…At early stages of opioid use disorder, sexual desire is originally stimulated but then drops to lower levels that at baseline [15][16][17]. Studies from Vietnam and Ukraine, where opioid use is predominated, reported that between 40 and 66% of male PWID were sexually active in the past 6 months [18][19][20]. The reduced sexual exposure leads to the lower rates of STI, including syphilis, chlamydia, and HIV, among more frequent users of opioids [21].…”
Section: Introductionmentioning
confidence: 99%
“…At early stages of opioid use disorder, sexual desire is originally stimulated but then drops to lower levels that at baseline [15][16][17]. Studies from Vietnam and Ukraine, where opioid use is predominated, reported that between 40 and 66% of male PWID were sexually active in the past 6 months [18][19][20]. The reduced sexual exposure leads to the lower rates of STI, including syphilis, chlamydia, and HIV, among more frequent users of opioids [21].…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam is a prime country example of an HIV epidemic that has been primarily driven by injection drug use. Vietnam has over 271,000 PWID in the country [9] with an HIV prevalence among PWID in different provinces ranging from 17 to 25% [10][11][12]. In 2014, the 90-90-90 targets were launched by the Joint United Nations Programme on HIV/AIDS: 90% of all people living with HIV will know their HIV status; 90% of all people with diagnosed HIV infection will receive sustained antiretroviral therapy, and 90% of all people receiving antiretroviral therapy will have viral suppression [13].…”
Section: Introductionmentioning
confidence: 99%